Jejak Peradaban Islam dan Tamadun Melayu di Brunei - Mariana, Abdul Halim; Pelawi, Afrio Ifaldo (PERADA, 2024)
The history and civilization in Brunei has deep roots in Islam and Malay Civilization, creating a rich and complex cultural and religious framework. This research aims to analyze the traces of Islamic civilization and Malay civilization in shaping identity in Brunei through historical, philosophical, sociological, and geographical approaches. This research uses qualitative methods through historical, sociological and philosophical approaches whose data collection instruments use library research. The data in this study were taken from various literature studies related to the traces of Islamic civilization and Malay civilization in Brunei. The results of the study show that the history of the entry of Islam in Brunei is researched by paying attention to the role of Muslim traders and intellectuals in the spread of this religion. Meanwhile, Malay Civilization in Brunei is understood through art, traditions, and cultural values that reflect Malay identity. Philosophical reviews delve into the roots of Islamic thought and Malay philosophy in Brunei society, while sociological reviews observe the impact of this civilization on the social structure and life of the community. Geographical analysis considers how geographical factors affect the culture and religious sites in Brunei. This research investigates the complex interactions between Islam and Malay Civilization in Brunei, providing in-depth insights into the cultural heritage and spirituality that shapes Brunei's identity.